Hypoplasia of the maxillary, sphenoid and frontal sinus in the patient with nasopharyngeal branchial cyst: Case Report - Matin Ghazizade (Journal of Research in Medical and Dental Science, 2016)
Cystic lesions of the nasopharynx are typically benign and often found incidentally. The authors report a case of nasopharyngeal branchial cyst in a patient with hypoplastic maxillary, sphenoid and frontal sinuses. The patient underwent transnasal endoscopic resection of the cyst.Results showed that in the management of nasopharyngeal branchial cyst it is important to clarify the anatomic details of the paranasal sinuses with Computed tomography (CT) scan respect to correct diagnosis and appropriate surgical planning. Nasopharyngeal branchial cysts and paranasal sinus hypoplasia may have the same developmental cause.